Comparison of short- and mid-term outcomes of Italian- and German-speaking patients after an interdisciplinary pain management programme in Switzerland: A prospective cohort study - Thomas Benz; Susanne Lehmann; Roberto Brioschi; Achim Elfering; André Aeschlimann; Felix Angst (Journal of Rehabilitation Medicine, 2019)

(untitled)
Objective: To quantify and compare the course of health-related quality of life of immigrant native Italian-speaking and German-speaking patients before and after an interdisciplinary pain programme. Design: Prospective cohort study with 1–12 month follow-up. Subjects: Fibromyalgia, generalized widespread pain, and chronic non-specific back pain patients (Italian-speaking n = 96, German-speaking n = 199). Methods: Score changes measured with the Short Form 36 (SF-36) were compared with multivariate analysis using standardized mean differences (SMD), adjusted for sex, education and the baseline score. Results: At baseline, health of the Italian-speaking patients was worse than for the German-speaking patients. Adjusted SMDs showed significantly better improvements in the German group compared with the Italian group: SF-36 Physical functioning SMD = 0.54 (at discharge) and 0.49 (at 12 months), General health SMD = 0.71 and 0.44, Vitality SMD = 0.43 and 0.48 in one sample. In the other sample, the corresponding SMDs were 0.06 (discharge), 0.50 (3 months) and 0.47 (6 months) for Bodily pain. Conclusion: State of health was better and health improvements were greater in German-speaking patients compared with Italian-speaking patients. Patients with a migration background may have special needs in therapeutic management, and addressing these might enhance the positive outcome in the short- and mid-term.